Microstructure evolution of peritectic Al–18 at.% Ni alloy directionally solidified in high magnetic fields. (20th June 2021) - Xiao, Yubao; Liu, Tie; Tong, Yuxin; Dong, Meng; Li, Jinshan; Wang, Jun; Wang, Qiang
Abstract: The effect of a high magnetic field on the microstructural evolution of a peritectic Al―18 at.% Ni alloy during directional solidification and its dependence on pulling speed were investigated. At a low pulling speed, the application of a 2 T magnetic field triggered the appearance of a primary Al3 Ni2 phase. At higher pulling speeds, a high magnetic field application induced primary Al3 Ni2 phase segregation that formed close to the central alloy regions. For all pulling speeds, the application of a high magnetic field induced bulk Al3 Ni/Al eutectic formation on the upper and lower parts of the alloys, and promoted elongated growth of the peritectic Al3 Ni phase along the magnetic field direction. Microstructural analysis indicated that microstructural evolution that was induced by high magnetic fields can be attributed to solute migration and melt flow that is regulated by magnetic, Lorentz, and thermoelectric magnetic forces and their coupling effects during peritectic solidification.